Dampak Revolusi Industri 4.0 Pada Dunia Pendidikan di Politeknik Negeri Sriwijaya - Titi Andriyani; Yusnizal Firdaus; Ummasyroh Ummasyroh (Jurnal Aplikasi Manajemen dan Bisnis, 2021)
This research raises the problem: a) What is the role and competence of lecturers at the Sriwijaya State Polytechnic in the era of the industrial revolution 4.0 ?, b) How to improve the quality of the education system at Sriwijaya State Polytechnic in facing the era of industrial revolution 4.0 ?. The model used for this research is to use a percentage of the respondents' answers. To see the percentage of respondents' answers to the questions on the questionnaire, the Score Index formula (Is) is used. Data analysis used in this research is by collecting data which is then processed using quantitative analysis and qualitative analysis. Research results: 1) Lecturer Competence Variable in the Educational Revolution Era 4. 0 on the Information and communication technology literacy indicator occupies the highest average IS with a score of = 85.91%, while the Creativity and innovative skills indicator has the lowest score with an average IS = 82.19%. 2) Educational System Variables: the human literacy indicator occupies the highest average IS with a score = 87.65%, while the digital literacy indicator occupies the lowest score with an average IS = 84.58%.